Exploring the Potential of Pluchea Indica L. Leaves from Muara Gembong, Bekasi, as a Functional Snacks - Andini Putri Riandani; Supriyanto Supriyanto; Mimah Mutmainah; Ricki Chandra Suyahya (Universitas Islam Raden Rahmat, Malang, 2025)
Muara Gembong, Indonesia, hosts a rich yet degraded mangrove ecosystem that plays a vital ecological and economic role. One plant species found abundantly in this ecosystem is Pluchea indica L., a mangrove-associated shrub with proven pharmacological properties. This study aimed to explore the nutritional potential and initial consumer acceptance of Pluchea indica L. leaves as a functional food product. Fresh leaves were collected from Pantai Bahagia Village and subjected to proximate and total phenolic content analysis. The results showed that the leaves contain 83.77% moisture, 5.25% protein, 0.52% fat, 6.10% carbohydrate, 2.97% ash, 1.12% crude fiber, and 1,324 mg/kg total phenolic compounds. Compared to other leafy plants such as Moringa oleifera and Sauropus androgynus, Pluchea indica L. leaves offer competitive nutritional and antioxidant value. To assess consumer acceptance, a simple snack product in the form of “peyek” was prepared and evaluated through a 5-point hedonic sensory test. The overall liking scores ranged from 3.25 to 4.5, indicating moderate to high acceptance. These findings suggest that Pluchea indica L. has promising potential as a sustainable, locally sourced functional food, aligning with environmental conservation and community empowerment efforts, particularly in supporting SDG 1 (No Poverty) and SDG 14 (Life Below Water).